Enzymes of energy technology - Armstrong, Fraser (Methods in enzymology, 2018)
Enzymes of Energy Technology, Volume 613 in the Methods in Enzymology series, highlights new advances in the field, with this updated volume presenting interesting chapters written by an international board of authors. Chapters include Purification of fully active and crystallizable photosystem II from thermophilic cyanobacteria, Production and manipulation of [NiFeSe]-hydrogenases for renewable hydrogen research, Hydrogen production by [FeFe]-hydrogenases, Production and properties of enzymes that activate and produce carbon monoxide, Recombinant [NiFe]-hydrogenases from E. coli, Working with nitrogenase, Oxygen--tolerant [NiFe]-hydrogenases, Cytoplasmic and Membrane Bound Hydrogenases from the hyperthermophile Pyrococcus furiosus, and more. Additional sections cover Enzymatic conversion of methane into useful chemicals, Production and investigations of trans-membrane electron transfer protein, Characterization of post-translational modifications in methyl-coenzyme M reductase in diverse methanogens by mass-spectrometry, Reductive activation of carbon dioxide by formate dehydrogenases, and Lytic polysaccharide monooxygenases in biofuel processing. 14. Production and manipulation of blue copper oxidases for technological applications Yasmina Mekmouche.